Frailty is associated with objectively assessed sedentary behaviour patterns in older adults: Evidence from the Toledo Study for Healthy Aging (TSHA). - Borja Del Pozo-Cruz; Asier Mañas; María Martín-García; Jorge Marín-Puyalto; Francisco J García-García; Leocadio Rodriguez-Mañas; Amelia Guadalupe-Grau; Ignacio Ara (PLoS ONE)
Objective The aim of this study was to examine the association of sedentary behaviour patterns with frailty in older people. Setting Clinical setting. Design Cross-sectional, observational study. Participants and measurements A triaxial accelerometer was used in a subsample from the Toledo Study for Healthy Aging (519 participants, 67-97 years) to assess several sedentary behaviour patterns including sedentary time per day, the number and duration (min) of breaks in sedentary time per day, and the proportion of the day spent in sedentary bouts of 10 minutes or more. Frailty was assessed using the Frailty Trait Scale (FTS). Regression analysis was used to ascertain the associations between sedentary behaviour patterns and frailty. Results Sedentary time per day and the proportion of the day spent in sedentary bouts of 10 minutes or more, were positively associated with frailty in the study sample. Conversely, the time spent in breaks in sedentary time was negatively associated with frailty. Conclusion In summary, breaking up sedentary time and time spent in sedentary behaviour are associated with frailty in older people.